Bilateral choroidal detachment and myopic shift after acetazolamide intake for laser capsulotomy. Issue 1 (January 2022) - Musetti, Donatella; Nicolò, Massimo; Bagnis, Alessandro; Cutolo, Carlo Alberto; Traverso, Carlo Enrico
Introduction: To report a case of bilateral choroidal effusion after laser capsulotomy. Case description: A healthy 85 years old white woman was referred to our hospital with a diagnosis of posterior capsule opacification in the left eye. The patient was treated with laser capsulotomy and oral acetazolamide was administered after the procedure. The day after, the patient visited the emergency room complaining bilateral blurred vision. A myopic shift and peripheral choroidal detachment was noted in both eyes. Discontinuation of acetazolamide and treatment with topical steroid and cyclopentolate resulted in a significant improvement in visual acuity and the complete resolution of the choroidal detachment in 1 week. Conclusion: To the best of our knowledge, this is the first reported case of choroidal detachment and acute transient myopia following the administration of oral acetazolamide after laser capsulotomy.